Analisis Nilai-Nilai Karakter Pada Cerita Rakyat Bujang Kurap di Kota Lubuklinggau - Muhammad Andre Julian; Agus Susilo; Isbandiyah Isbandiyah (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2023)
This study aims to analyze the character values in the Bujang Kurap story in Lubuklinggau City. The research method used is descriptive method. Data collection techniques in this study used interview and documentation techniques. The data analysis technique was carried out with Miles and Huberman's interactive data analysis model. The results of the study describe the values contained in the Bujang Kurap Folklore. The story of Bujang Kurap is a story from the Lubuklinggau community which has become oral literature which contains the values of local wisdom. The story of Bujang Kurap is a legend because it tells of the occurrence of Lake Raya, namely when there was a contest for pulling sticks in Karang Panggung Village. The Bujang Kurap story has the following character values: can provide entertainment, supernatural powers, patience, belief in God, honesty, and not arrogant attitude. The character values contained in the Bujang Kurap story are a medium of learning for the younger generation. This legend continues to be an oral literature that must be guarded so as not to be eroded by globalization. Folklore, especially in today's society, has begun to fade, this is because the story connection from the older generation has been cut off. Meanwhile, the younger generation today is very little willing to dig into the history of folk tales. The younger generation today is more inclined to the world of increasingly sophisticated technology. Folklore is only considered as entertainment alone, no meaning is taken from the stories conveyed.